ANALISIS LAJU KOROSI BESI BETON DENGAN MEDIUM TANAH RAWA - Rahmaniah, Rahmaniah; Amalia, Nurul; Ihsan, Ihsan (JFT: Jurnal Fisika dan Terapannya, 2019)
The research on corrosion rate analysis of concrete iron with swamp soil medium has been conducted. The aims of this study were to determine the corrosion rate and the types of corrosion that occurred in concrete iron with swamp soil medium. The methods of this study are Weight Loss method, Atomic Absorption Spectroscopy (AAS) test, and Scanning Electron Microscope-Energy Dispersion X-Ray (SEM-EDX). This study used a different immersion time variant, such as 20 days, 40 days, 65 days, and without medium for 65 days. The concrete iron used in this study is concrete U-24 or plain concrete iron 10. The corrosion rate that occurs in iron concrete with swamp soil medium at 20 days immersion is 20977.5868 mmpy, 40 days immersion is 17721.9174 mmpy, 65 days immersion is 16932. 9071 and 65 days without a medium are 3023.3793 mmpy. The more time, the rate of corrosion become more slowly due to the influence of corrosion products that have occurred. The corrosion rate without the medium is slower than the corrosion rate with the medium. The types of corrosion that occurs in concrete iron with swamp soil medium are crevice corrosion and pitting corrosion.